Investigation on a new hole-flanging approach by incremental sheet forming through a featured tool. (November 2016) - Cao, Tingting; Lu, Bin; Ou, Hengan; Long, Hui; Chen, Jun
Abstract: One of the major challenges in conventional incremental sheet forming (ISF) is the extreme sheet thinning resulted in an uneven thickness distribution of formed part. This is also the case for incrementally formed parts with hole-flanging features. To overcome this problem, a new ISF based hole-flanging processing method is proposed by developing a new ISF flanging tool. Comparative studies are conducted by performing hole-flanging tests using both ISF conventional ball-nose tool and the new flanging tool to evaluate the sheet deformation behavior and the quality of the final part. Stress distribution and strain variation are investigated by analytical approach and numerical simulation. Experiments have been conducted to validate the analytical model and simulation results, and to further study the fracture behavior. Results show that the new flanging tool generates greater meridional bending than stretching deformation in conventional ISF. The combination of bending-dominated deformation mode with localized deformation of ISF ensures more uniform thickness distribution on hole-flanging part with better resistance to fracture. Highlights: Developed a new hole flanging process by incremental sheet forming using a new tool. Established an analytical model to investigate the deformation mechanism. Improved the hole-expansion ratio by 130% with more uniform thickness distribution.